Novel carbon dots with dual Modulatory effects on the bone marrow and spleen as a potential therapeutic candidate for treating spinal cord injury - Junjin Li; Hongda Wang; Yuanquan Li; Chunzhen Wang; Haiwen Feng; Yilin Pang; Jie Ren; Chuanhao Li; Erke Gao; Dejing Zhang; Dunxu Hu; Pengtian Zhao; et al. (Bioactive Materials)
Spinal cord injury triggers leukocyte mobilization from the peripheral circulation to the injury site, exacerbating spinal cord damage. Simultaneously, bone marrow hematopoietic stem cells (HSCs) and splenic leukocytes rapidly mobilize to replenish the depleted peripheral blood leukocyte pool. However, current treatments for spinal cord injuries overlook interventions targeting peripheral immune organs and tissues, highlighting the need to develop novel drugs capable of effectively regulating peripheral immunity and treating spinal cord injuries. In this study, we designed, synthesized, and characterized novel Ejiao carbon dots (EJCDs) that inhibit myeloid cell proliferation and peripheral migration by promoting HSC self-renewal, and distinct differentiation into erythroid progenitors in vitro and in vivo. Additionally, EJCDs attenuate the immune response in the spleen, leukocytes’ reservoir, following spinal cord injury by diminishing the local infiltration of monocytes and macrophages while promoting motor function recovery. These effects are mediated through the downregulation of CCAAT enhancer binding protein-β expression in the spleen and the upregulation of FZD4 protein expression in Lin− Sca-1+ c-kit+ cells (LSKs) within the bone marrow. Our findings demonstrate that EJCDs effectively reduce myeloid cell infiltration post-spinal cord injury and promote neurological recovery, making them promising therapeutic candidates for treating spinal cord injuries.